Extraction, Identification and comparison of Organically chemical components in extractive of bark and wood from Eucalyptus by Gas chromatography - Mass spectrometry - milad tajik; ramin vaysi; majid kiaei (تحقیقات علوم چوب و کاغذ ایران, 2014)
This research was carried out to identification and comparison of organically chemical component in the wood / bark extractives Eucalyptus camaldulensis. Three healthy trees were cut down from Nowshahr forest and samples were converted into the wood flour. The extractives was prepared with acetone solvent according to TAPPI standard, then transfer to the ballon and then the BSTFA catalyst was added and transfer to the GC / MS injections. Identification of components was done according to the retention time curve, calculation of Kovats correlation and Adams table. Out of 13 components in the bark of Eucalyptus and 18 components in that wood, 2 constituents such as Bis (2 - ethyl hexyl) phthalate and hexadecanoic acid was detected as the same. The most important of chemical component in the bark is (2 _ ethyl hexyl) phthalate (98.72 %). 2 - Pentanone (57.41 %) was important component in the eucalyptus wood .